Intelligent vibration control in civil engineering structures - Xu, Zhao-Dong; Guo, Ying-Qing; Zhu, Jun-Tao; Xu, Fei-Hong (Academic Press is an imprint of Elsevier : Zhejiang University Press, 2016)
Intelligent Vibration Control in Civil Engineering Structures provides readers with an all-encompassing view of the theoretical studies, design methods, real-world implementations, and applications relevant to the topic The book focuses on design and property tests on different intelligent control devices, innovative control strategies, analysis examples for structures with intelligent control devices, and designs and tests for intelligent controllers. Focuses on the principles, methods, and applications of intelligent vibration control in civil engineering Covers intelligent control, including active and semi-active control Includes comprehensive contents, such as design and properties of different intelligent control devices, control strategies, and dynamic analysis, intelligent controller design, numerical examples, and experimental data.